Ontogenetic change of body color patterns in laboratory-raised juveniles of six terrestrial hermit crab species - Hamasaki, Katsuyuki; Tsuru, Takuma; Sanda, Tetsuya; Fujikawa, Shunsuke; Dan, Shigeki; Kitada, Shuichi (Zootaxa, 2017)
We examined the ontogenetic change of body color patterns in the laboratory-raised juveniles of six terrestrial hermit crab species, including Birgus latro, Coenobita brevimanus, C. cavipes, C. purpureus, C. rugosus, and C. violascens, which commonly occur in the southern islands, Japan. The body color patterns of coenobitid juveniles were species-specific. The diagnostic features of body color patterns enable identification of juveniles of coenobitid crab species in the wild, thereby helping to understand the precise habitats of each coenobitid species.